6(x-5)-3(x+1)=

Simple and best practice solution for 6(x-5)-3(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-5)-3(x+1)= equation:


6(x-5)-3(x+1)=0

We simplify the equation to the form, which is simple to understand
6(x-5)-3(x+1)=0

Reorder the terms in parentheses
+(+6x-30)-3*(x+1)=0

Remove unnecessary parentheses
+6x-30-3+*(+x+1+)=0

Reorder the terms in parentheses
+6x-30+(-3x-3)=0

Remove unnecessary parentheses
+6x-30-3x-3=0

We move all terms containing x to the left and all other terms to the right.
+6x-3x=0+30+3

We simplify left and right side of the equation.
+3x=+33

We divide both sides of the equation by 3 to get x.
x=11

See similar equations:

| 36x-y=98 | | 25x^2-7=9 | | 5x^2+12x=-2 | | 6x^2-y=-2 | | 5y+8=32 | | 3r^2-7r+8=0 | | 2t^2+1=19 | | 5(3+4x)-6=149 | | 2w^2-72=0 | | 4k+8=24 | | a^2=28 | | 2(3x+2)+4=26 | | (2n+1)=3n^2 | | 5x+2x=75 | | (2x+1)=3n^2 | | 5*(x-1)+20=40*(x-3) | | 4B+36=3(20)-2B | | x(5-2x)=0 | | 3(m-2)=3(2m+3) | | x+0.3(150000)=150000 | | 2[x-7]=3x | | ln(x+2)=5 | | 102300+0.3x=x | | 2.3-n=4n-3.2 | | 6(t+8)-2t=3t-19 | | 72+2w=44 | | x^3-10x^2+33x-34=0 | | 3d+5=2d+6 | | 100000+0.3x=x | | 132418+0.3x=x | | 0.3x+25=x | | (47x+24y)+(35x+39y)= |

Equations solver categories